The Role of the Family Hope Program (PKH) in Enhancing Family Literacy and Financial Management from the Perspective of Islamic Economics - Muh. Akbar; Mukhaer Pakkanna (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
As Financial Planner, women have a challenging task, as managing family finances is akin to regulating the heartbeat of married life, making financial literacy and management essential skills to possess. This research examines the role of the Family Hope Program (PKH) in educating aid recipients regarding financial management, focusing on female PKH aid recipients who must actively seek livelihoods. This study adopts a qualitative approach with a case study methodology. The research findings highlight the vital role of PKH in enhancing beneficiaries' financial management literacy, aligning with Islamic economics principles. It is evident in all informants demonstrating financial management practices adhering to Islamic economic principles. It includes using money, budgeting, setting aside emergency/savings funds investments, and managing credit/debt. These findings serve as a crucial reference for PKH support. Recommendations for future research include exploring the differences in financial management between active and non-working PKH aid recipients.